Gestión financiera de los ingresos del centro de capacitación y conducción de manejo Center Drive Compañía Limitada años 2019-2020-2021. - Merchán Mendieta, Jean Carlos (2022)
The lack of an analysis referencing one of the most important aspects of any company, as is the item of income, is a point of view to keep in mind, studying its evolution sets a clear precedent as it determines the situations to be taken into account in decision-making, since the implementation of unsuccessful resolutions affects not only the income of a company, but can also compromise its operations and even put the institution at risk of bankruptcy. This case study is developed in the limited liability company "Center Drive" Babahoyo branch, this is an institution dedicated to the teaching, training and driving of vehicular driving. The financial management is carried out through the analysis of the financial statements of the company and the application of various financial ratios, established based on the requirements of the needs of the company, the methodology applied is given through the deductive method, using tools such as observation and interview to obtain information from first source to analyze the financial information without any inconvenience, this in order to establish appropriate conclusions after the course of financial management mentioned. The purpose of this research work is to provide a perspective on how important it is to take into consideration the different evolutions and the causes of these changes in the income items, as well as to study and analyze them in detail.